DESAIN KAMPUNG SUSUN DENGAN PENERAPAN ARSITEKTUR MODULAR SEBAGAI CITRA BARU PERMUKIMAN DAN AKUPUNKTUR KAWASAN MUARA BARU - Amanda Augustine; Budi Adelar Sukada (Jurusan Arsitektur dan Perencanaan, 2022)
Muara Baru area is experiencing housing class disparities, overcrowding, a lack of inclusive facilities, and the degradation of the movement and physical image of the settlements that are getting worse. Some residents of Muara Baru live on the edge of the reservoir. It is necessary to relocate the residents of illegal settlements from the edge of the reservoir to order settlements; have supporting facilities to fulfill their needs; improve the image of the area. One of the architectural solutions that can be applied is an housing complex with social and public facilities, and is located in a new site. The purpose of the design is to propose: architectural solutions that can accommodate all residents of illegal settlements on the edge of the reservoir; the spatial and design elements of the Modular Vertical Housing that can improve the welfare of the residents of the reservoir edge, the quality and image of the settlements; Modular Vertical Housing which can create a new image of the Muara Baru settlement by processing the mass of the building and its outer space The literature review contains theories about slum housing, urban acupuncture, city’s image, and vertical rental housing that can be applied as a basis for designing. The design method departs from the existing varied patterns of illegal settlements, then makes 3 types of residential modules, and the embodiment of varied and order arrangement of modules. With the creation of an order residential area through the Modular Vertical Housing, this project can become acupuncture of the area and a new image of the settlement, as well as the value of the area, residents' economy, movement can be increased. Keywords: Modular Vertical Housing; Muara Baru; New image of the settlement Abstrak Kawasan Muara Baru mengalami kesenjangan kelas perumahan, kepadatan yang terlalu tinggi, kurangnya jumlah fasilitas yang inklusif, dan degradasi pergerakan serta citra fisik permukiman yang semakin buruk. Sebagian warga Muara Baru bermukim di bibir waduk. Diperlukan relokasi warga permukiman ilegal dari bibir waduk ke permukiman beraturan; adanya fasilitas pendukung untuk memenuhi kebutuhan mereka; peningkatan citra kawasan. Salah satu solusi arsitektur yang dapat diterapkan adalah kampung susun dengan fasilitas sosial dan umum, serta terletak di tapak baru. Tujuan perancangan adalah mengusulkan: solusi arsitektur yang dapat mewadahi seluruh warga permukiman ilegal bibir waduk; keruangan dan elemen desain Kampung Susun Modular yang dapat meningkatkan kesejahteraan warga bibir waduk, kualitas dan citra permukiman; Kampung Susun Modular yang dapat membuat citra baru permukiman Muara Baru dengan pengolahan massa bangunan dan ruang luarnya. Kajian literatur berisi teori mengenai perumahan kumuh, akupunktur perkotaan, citra kota, dan rumah susun sederhana sewa yang dapat diterapkan sebagai dasar perancangan. Metode desain berangkat dari pola permukiman ilegal eksisting yang bervariatif, kemudian membuat 3 tipe modul hunian, dan perwujudan susunan modul yang variatif dan beraturan. Dengan terciptanya kawasan permukiman beraturan melalui Kampung Susun Modular, proyek ini dapat menjadi akupunktur kawasan dan citra baru permukiman, serta nilai kawasan, ekonomi warga, pergerakan dapat ditingkatkan.